Pentingnya Islam dalam Berbisnis di Era Generasi Z: The Importance of Islam in Doing Business in the Generation Z Era - Nurfitriani Widodo, Wahyu; Vita Ayu Mei Kusuma; Nurvita Septiayu Putri Widya; Aulia Azzahra; Shine Afiatun Jannah; Vannisa Yunanda Aiiya Ramadanti; Ahmad Nurrohim (Litera Academica Publishing, 2024)
This study analyzes the development of Islamic business in the Gen Z era with a focus on Islamic values in doing business in the Gen Z era as well as technological challenges and opportunities. Through a quantitative descriptive approach, using literature studies and summaries previous research results. The results of the research show that Islamic values such as faith, honesty and the spirit of hard work have a significant influence on the formation of entrepreneurial character in generation Z. This research concludes that education based on Islamic values can be the basic capital for the younger generation to become successful entrepreneurs. successful and of noble character.